2020
DOI: 10.1007/s00330-020-06824-7
|View full text |Cite
|
Sign up to set email alerts
|

Solving the preoperative breast MRI conundrum: design and protocol of the MIPA study

Abstract: Despite its high diagnostic performance, the use of breast MRI in the preoperative setting is controversial. It has the potential for personalized surgical management in breast cancer patients, but two of three randomized controlled trials did not show results in favor of its introduction for assessing the disease extent before surgery. Meta-analyses showed a higher mastectomy rate in women undergoing preoperative MRI compared to those who do not. Nevertheless, preoperative breast MRI is increasingly used and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 46 publications
(47 reference statements)
0
21
0
1
Order By: Relevance
“…Despite several studies have progressively promoted the role of breast MRI to complete conventional imaging for preoperative staging, due to evidence-based benefits, the limited number of randomized clinical trials (22)(23)(24)(25)(26) that evaluated the impact of preoperative MRI on treatment regimens and surgical outcomes have given conflicting results. A large-scale observational multicenter prospective study (MIPA study) was launched internationally in 2012 but is currently at the analytic phase (27). As a consequence, the role of preoperative breast MRI remains controversial for now, and alternative imaging modalities have been considered to evaluate the extent of disease during the preoperative planning.…”
Section: Discussionmentioning
confidence: 99%
“…Despite several studies have progressively promoted the role of breast MRI to complete conventional imaging for preoperative staging, due to evidence-based benefits, the limited number of randomized clinical trials (22)(23)(24)(25)(26) that evaluated the impact of preoperative MRI on treatment regimens and surgical outcomes have given conflicting results. A large-scale observational multicenter prospective study (MIPA study) was launched internationally in 2012 but is currently at the analytic phase (27). As a consequence, the role of preoperative breast MRI remains controversial for now, and alternative imaging modalities have been considered to evaluate the extent of disease during the preoperative planning.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative contrast-enhanced breast MRI has emerged as a solution, but neither the COMICE [ 13 ] nor the MONET [ 14 ] trial found an associated benefit. Additional studies are needed to further exploit additional MRI information and techniques to be applied in the surgical theater [ 15 ]. Intraoperative US (as an additional tool to standard localization techniques) has been used successfully to some extent to reduce positive margins, therefore reducing re-operation rates [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should investigate the effect on prognosis by comparing patients in whom MRI findings led to a change in treatment plan with those without treatment change and/or patients without MRI. For instance, the currently recruiting European wide MIPA trial could identify this specific subgroup of patients allowing to investigate prognosis in these patients into detail [ 20 ].…”
Section: Discussionmentioning
confidence: 99%